Enhancing Secrecy Capacity in FSO Links via MISO Systems Through Turbulence-Induced Fading Channels With Misalignment Errors - Ruben Boluda-Ruiz; Sezer Can Tokgoz; Antonio Garcia-Zambrana; Khalid Qaraqe (IEEE Photonics Journal)
It has recently been proved that the free-space optical (FSO) communication links are susceptible to interceptions. Due to this reason, the optics community shows a special interest in studying these high-speed links in greater detail from a physical layer security (PLS) point of view. Therefore, in this paper, we propose, for the first time, enhancing the average secrecy capacity (ASC) in FSO links via multiple-input/single-output (MISO) systems. It is well-known that the fading effects in FSO channels can be significantly mitigated by exploiting spatial diversity techniques at the transmitter end. Thus, we develop a new asymptotic closed-form solution at high signal-to-noise-ratio (SNR) to accurately compute the ASC for MISO based FSO communication systems with equal gain combining (EGC) reception through generalized misalignment and atmospheric turbulence-induced fading channels. As a key feature, we investigate the impact of the eavesdropper's orientation along with its location in the pointing error model. We can conclude that the influence of the eavesdropper on recollecting radiated power is diminished considerably by increasing not only the normalized beam width at the receiver end, but also by increasing the number of laser sources. Numerical results are tested by exact Monte Carlo simulations.